Tethered women, mobile men: Gendered mobilities of typewriting. (May 2020) - Plotnick, Rachel
In recent years, scholars have turned their attention to the nexus of mobility, space, and communication practices. At the same time, historians of information and communication technologies (ICTs) have amassed a large body of literature on the history of typewriters and their contribution to gendered office work. To date, however, these two strains have yet to converge. This article thus examines intersections between typewriting, gender, and mobility, focusing on the case of portable typewriters to investigate users' "differential" mobilities before World War II in the United States. In this regard, it reconceives of typewriters as fluid historical objects defined significantly by their social contexts. It calls upon scholars to expand their characterizations of typing beyond thinking only of it as an immobile, desk-based practice and as "women's work." Instead, it draws attention to itinerant male typists as an early class of portable typewriter users who could (and were encouraged to) travel with a typewriter in tow. More broadly, the article also contributes to understandings of mobile media histories beyond mobile phones by demonstrating similar concerns related to portability, usability, and ergonomics in the early 20th century.